Climatic and environmental conditions in the Western Galilee, during Late Middle and Upper Paleolithic periods, based on speleothems from Manot Cave, Israel. Issue 160 (November 2021) - Yasur, Gal; Ayalon, Avner; Matthews, Alan; Zilberman, Tami; Marder, Ofer; Barzilai, Omry; Boaretto, Elisabetta; Hershkovitz, Israel; Bar-Matthews, Miryam
Abstract: Early Ahmarian, Levantine Aurignacian and Post-Levantine Aurignacian archeological assemblages show that the karstic Manot Cave, located 5 km east of the Mediterranean coast in the Western Galilee region of Israel, was intensively occupied during the Early Upper Paleolithic. The coexistence of these rich archaeological layers with speleothems in Manot Cave provides a window of opportunity for determining the relationships between climatic conditions and the nature of human activity and mobility patterns in the Western Galilee region during the Early Upper Paleolithic period. This study, based on four stalagmites that grew almost continuously from ∼75 to 26.5 ka, covers most of the last glacial, and overlaps with the human occupation of the cave. The speleothems oxygen (δ 18 O) and carbon (δ 13 C) isotopic records indicate that climate and environmental conditions fluctuated during the last glacial, some of which correspond with Dansgaard–Oeschger (D-O) cycles 12, 10, 7 and Heinrich (H) events VI and V. Consistent with independent evidence from botanic and faunal remains, these climatic shifts brought about significant environmental changes in the region, ranging from dominant thick Mediterranean forest to more open landscape. A good correlation with less negative δ 13 C values is most pronounced during the Early Ahmarian time period, but there was also a change to less negative δ 13 C values during the Levantine Aurignacian and Post-Levantine Aurignacian industries in the Levant. These positive δ 13 C shifts suggest that environmental transformation towards a more open grassy landscape dominated by C4 vegetation might have played an important role in the development of these cultural entities (mainly the Early Ahmarian) in Manot Cave region.